Detecting mining-induced ground deformation and associated hazards using spaceborne InSAR techniques. Issue 1 (1st January 2018) - Zhang, Albert; Lu, Jason; Kim, Jin-Woo
ABSTRACT: The Delaware Basin, an evaporite sequence spanning west Texas and southeast New Mexico, is well known for the mining of potassium salts, known as potash. Several companies operate mines in the region, primarily using room-and-pillar techniques. However, the region's karst topography is prone to ground subsidence and sinkhole development when triggered by anthropogenic activities. We explored a region of significant ground subsidence encompassing a potash mine. Incorporating synthetic aperture radar (SAR) images from the advanced land-observing satellite (ALOS) and Sentinel-1A sensors, we used interferometric SAR techniques to detect a significant amount of subsidence located in several distinct areas from 2007 to 2011 and from January to November 2016. To investigate the origin of this subsidence, we considered potash mining by analysing the mine operator's production records. We observed a strong correlation between the total subsidence rate in our area and the potash production rate during 2007–2011. Furthermore, we observed a considerable amount of continuous subsidence during 2016, despite the mine operator suspending potash production on 6 May 2016. As such, the observed subsidence could result in deleterious consequences throughout the region if further action is not taken.